ChemInform Abstract: Natural Inorganic Nanoparticles — Formation, Fate, and Toxicity in the Environment. Issue 1 (17th December 2015) - Sharma, Virender K.; Filip, Jan; Zboril, Radek; Varma, Rajender S.
Abstract: Review: 53 refs.